Improving Space Probes at Skyworld Indonesia TMII to Become the Main Destination of Astronomy Education Using Micro Grounded Theory - Sari, Irma Ratna; Heikal, Jerry (CV. ULIL ALBAB CORP, 2025)
The tourism sector is one of the business industries that has a great contribution to the development of the national and regional economy, job creation and cultural promotion media. Ideally, every tourist attraction must have a sustainable development strategy, so that it can continue to bring in visitors and not lose its attraction even though it is in the midst of increasingly proliferated and diverse tourism business competition. There are not many tourism industries in Indonesia that develop tourism in the field of space education. Skyworld Indonesia is the only vehicle that focuses on space, aeronautics and technology education modules. Skyworld Indonesia is the originator of space education rides located in the tourist area of Taman Mini Indonesia Indah (TMII) East Jakarta, established in 2016, now Skyworld Indonesia is trying to develop its rides so that in the future Skyworld can run in accordance with the Vision and Mission as the only main destination for technology-based space education tourism in Indonesia. The method used in this study is micro-theory research. The research was conducted through a direct interview with one of the speakers, namely the President Director of Skyworld Indonesia. The main factor obtained from the results of this study is that Skyworld must develop technology for simulators (products) that are still conventional, few and simple need to be upgraded to more modern and technology-based products (simulators), then continue with improvements in terms of physical buildings, increase promotion on social media and increase the development of Human Resources (HR).